Pelaksanaan Transaksi Jual Beli Tanah dengan Sistem Perantara (Makelar) Berdasarkan Peraturan Menteri Perdagangan Nomor 51 Tahun 2017 tentang Perusahaan Perantara Perdagangan Properti - Karim, Asma (Institut Agama Islam Negeri Metro, 2023)
This study aims to know and analyze the process of implementing land sale and purchase using a broker based on the regulation of the minister of trade number 51 of 2017 concerning property trading companies and to find out and analyze the legal responsibilities of the parties if there are legal problems in the future land sale and purchase transaction in Wates sub-district, Kulon Progo Regency. His research methods are empirical juridical based on primary data as well as secondary data. The results showed that based on primary data from interviews with individual brokers in Kulonprogo, it is known that in principle in the process of buying and selling property with the intermediary of brokers, which are individuals or individuals, most of the procedures are almost the same as the processes applied to companies incorporated in the Regulation of the Minister of Trade Number 51 of 2017. It can be seen that the procedure is that the broker generally makes an oral agreement, followed by a written agreement which is generally underhand, providing the choice of location needed by the buyer, verifying data from the landowner to check the authenticity of land ownership; assist the process of transactions with sellers when buyers are interested in buying the desired location; then the broker and seller bring land data to be transacted at the PPAT Notary; Further about the legal responsibility of the parties in the event of legal problems in the land sale and purchase transaction in the future, namely, brokers, and service users should make contracts that affirm the rights and obligations of the parties, in addition to affirming the legal responsibilities that must be borne by the parties in the event of adverse defaults in the future.